P&G a safe bet under economic instability - the main drivers - Soares, Shanty Maria de Jesus (2022)
This Equity Research was developed as one of the requirements to complete the Master Degree in Finance. Equity Research is an essential material in assisting investors decisions as it provide them with detailed financial analysis of the under-study company as well as a recommendation whether to sell, hold or buy a particular investment opportunity. In this equity research the company under study is Procter & Gamble, indicating a price target in December 2023. In order to do so, a crucial financial analysis was developed by analyzing the company´s industry, the historical financial performance, the main macroeconomic risks, the competitors. The forecast of the annualized income statement and cash flows was developed taking into account reasonable projections by performing a DCF valuation.